SEJARAH LAHIRNYA NEGARA BANGLADESH - Arki Auliahadi (Tamaddun, 2018)
Due to many differences such as language, dress and way of life with West Pakistan, there was a desire to separate and break relations with Pakistan, so that from some of these factors, the determination of the people of East Pakistan to separate from West Pakistan. After East Pakistan officially separated from West Pakistan, the name of East Pakistan changed to Bangladesh, which had thousands of Dakka cities. Through hard and persistent efforts, East Pakistan gained its independence from West Pakistan, namely the official founding of the state of Bangladesh. The independence and founding of the Bangladesh State is inseparable from the struggle of Bangladeshi figures, including Sheikh Mujiburrahman, who later became an important figure in the history of Bangladeshi independence figures.